Impact of early biochemical diagnosis of anastomotic leakage after rectal cancer surgery: long-term results from GRECCAR 5 trial. Issue 6 (13th February 2021) - Denost, Q; Rouanet, P; Faucheron, J -L; Panis, Y; Meunier, B; Cotte, E; Meurette, G; Portier, G; Sabbagh, C; Loriau, J; Benoist, S; Piessen, G; et al.
Abstract : Elevated C-reactive protein, should be used to prompt early detection of AL prior to the development of clinical symptoms. Early biochemical diagnosis and intervention of AL mitigates the negative impact of AL on oncological outcomes in patients with rectal cancer.